(untitled) (Hematology Meeting Reports, 2009)
Yttrium 90 (90Y) ibritumomab tiuxetan (Zevalin), a radiolabeled monoclonal antibody against the CD20 antigen, is indicated for the treatment of patients with relapsed or refractory low-grade, follicular, or transformed B-cell non-Hodgkin’s lymphoma (NHL) in the USA, including patients with rituximab-refractory follicular NHL. Data on 211 patients treated in 4 registrational USA clinical trials were analyzed to determining the number and characteristics of patients achieving long term durable responses and compare the efficacy and safety of 90Y ibritumomab tiuxetan when it was used after the first relapse of NHL and when it was used after 2 or more prior therapies. Sixty-three of the patients (30%) were treated with 90Y ibritumomab tiuxetan upon their first relapse and 148 (70%) after 2 or more prior therapies. TTP of ≥12 months was noted in 78 patients (37%) who were termed long term responders and were further characterized. Median age of the long term responders was 58 years (range 24-80) with 44% over 60 years. Notably, 59% 0f patients had received ≥2 prior treatments and 37% had failed to respond to immediate prior therapy. Median response duratin was 28.1 months (10-5-80.3 months). Median TTP was 53.9 months. If analyzed by number of prior treatments in the overall population, the complete response rate (confirmed [CR] and unconfirmed [CRu]) was higher in first-relapse patients (49% vs. 28%; p